2018
DOI: 10.3390/app8091435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crop Leaf Angle on LAI-Sensitive Narrow-Band Vegetation Indices Derived from Imaging Spectroscopy

Abstract: Leaf area index (LAI) is an important biophysical variable for understanding the radiation use efficiency of field crops and their potential yield. On a large scale, LAI can be estimated with the help of imaging spectroscopy. However, recent studies have revealed that the leaf angle greatly affects the spectral reflectance of the canopy and hence imaging spectroscopy data. To investigate the effects of the leaf angle on LAI-sensitive narrowband vegetation indices, we used both empirical measurements from field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…It can be summarized that the R 760 /R 730 and REIP might be suitable for estimating crop %N. It should, however, be further investigated how prone these VIs are to effects such as saturation [37], multiangular reflection [85], leaf inclination angle [43], or general atmospheric conditions. Further research should involve additional VIs, which were investigated for N content and N uptake, such as the red edge-based canopy chlorophyll content index [86] or the optimum multiple narrow band reflectance model [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be summarized that the R 760 /R 730 and REIP might be suitable for estimating crop %N. It should, however, be further investigated how prone these VIs are to effects such as saturation [37], multiangular reflection [85], leaf inclination angle [43], or general atmospheric conditions. Further research should involve additional VIs, which were investigated for N content and N uptake, such as the red edge-based canopy chlorophyll content index [86] or the optimum multiple narrow band reflectance model [31].…”
Section: Discussionmentioning
confidence: 99%
“…These problems can be avoided by using bidirectional spectrometers or active sensors [30,40,41]. Further limiting factors are, however, the influence of differing soil properties, which is particularly important in the early growing period due to the low vegetation fraction [42], and plant properties, such as the leaf inclination angle [43]. Measurements with field spectrometers can also cover only small parts of the crop canopy.…”
mentioning
confidence: 99%
“…These comprehensive factors are sufficient enough to blur the relationships between most SRIs examined and the measured parameters. Therefore, several studies have reported that to improve the fit of the relationship between SRIs and measured parameters, it is important to analyze these relationships using the pooled data of all treatments in order to avoid the heterogeneity occurring between these treatments, or design new SRIs to remove the adverse effects of multiple factors on the spectral properties of the canopy [ 29, 50, 5459 ]. For instance, Prabhakara et al [ 58 ] reported that many SRIs failed to differentiate between the amount of biomass in six winter cover crops when the biomass was too high or too low.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion reveals that the LAI retrieval improvements can exist in a time series LAI retrieval and generalize to wider corn planted areas. Much research has indicated that the retrieved LAI using a remote sensing technique is underestimated [50][51][52][53][54], especially for MODIS LAI [10,[44][45][46][47][48]. Therefore, the inferred leaf angle distribution improves the underestimation of LAI retrieval using remote sensing images.…”
Section: Discussionmentioning
confidence: 99%